The Influence of Leadership Style, Work Motivation and Work Culture Through Job Satisfaction on Employee Performance - Taufiqurrohman Taufiqurrohman; Nurul Badriyah; Evi Fitrotun Najiah (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the effect of leadership style, work motivation, and organizational culture on employee performance mediated by job satisfaction at CV. Build a Sub-Contractor Lamongan Design. The research employed a quantitative approach using cross-sectional design. Primary data were collected through questionnaires distributed to 49 employees using a census method. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results show that leadership style has a significant positive effect on employee performance (T=2.625, p=0.009), work motivation significantly affects both job satisfaction (T=2.924, p=0.004) and employee performance (T=2.182, p=0.030), and organizational culture significantly impacts employee performance (T=2.614, p=0.009). Job satisfaction also significantly influences employee performance (T=2.266, p=0.024). However, leadership style and organizational culture do not significantly affect job satisfaction, nor do they indirectly influence performance through job satisfaction as a mediating variable. Only work motivation showed significant mediation through job satisfaction (T=2.071, p=0.039). The R-square value of 74.1% indicates that the model strongly explains variance in employee performance. These findings suggest that improving work motivation and instilling a strong organizational culture are key strategies for enhancing employee performance in construction companies.